In vitro antibacterial activity and physicochemical properties of a crude methanol extract of the larvae of the blow fly Lucilia cuprina. Issue 4 (8th May 2013) - TEH, C. H.; NAZNI, W. A.; LEE, H. L.; FAIRUZ, A.; TAN, S. B.; SOFIAN‐AZIRUN, M.
Abstract: The emergence of multidrug‐resistant bacterial strains has prompted the reintroduction of maggot therapy in the treatment of chronic, infected wounds. Many previous studies have demonstrated the potent antibacterial activity of larval excretions/secretions of the blowfly Lucilia sericata (Meigen) (Diptera:Calliphoridae) against bacteria. However, the antibacterial activity of its sibling species, Lucilia cuprina (Wiedemann) (Diptera:Calliphoridae) against a wide range of pathogenic bacteria has never been determined. The aim of this study was to develop a new procedure to produce whole body extract of larvae of L. cuprina via methanol extraction as well as to demonstrate the in vitro antibacterial activity of this extract against seven selected wound pathogens ( Staphylococcus aureus, methicillin‐resistant S. aureus, S. epidermidis, Streptococcus pyogenes, Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli ). The turbidimetric assay demonstrated that L. cuprina larval extract was significantly potent against all bacteria tested ( P < 0.001). Additionally, colony‐forming unit (CFU), agar well diffusion and minimum inhibitory concentration assays have confirmed the apparent potency of larval extract against P. aeruginosa . The reconstituted larval extract was highly robust and thermally stable. These observations substantiated the feasibility of the methanol extraction method in the production of larval extract.